NLRP3 deficiency abrogates silica-induced neutrophil infiltration, pulmonary damage and fibrosis - Lam, Maggie; Barry, Kristian T.; Hodges, Christopher J.; Harpur, Christopher M.; Ong, James D. H.; Rosli, Sarah; West, Alison C.; Dousha, Lovisa; Hertzog, Paul J.; Mansell, Ashley; Tate, Michelle D. (Respiratory research, 2025)
Background Silicosis is a progressive and often fatal occupational lung disease. The NLRP3 inflammasome is an innate immune sensor that is activated by silica. Accumulating evidence has implicated a role for NLRP3 in silicosis pathogenesis. In this study, we mechanistically elucidated the contribution of NLRP3 to silica-induced pulmonary disease. Methods The in vivo role of NLRP3 was investigated following intranasal delivery of 2 mg of silica or diluent alone to wildtype, NLRP3 reporter, and NLRP3-deficient mice. Protein expression, inflammation, and histopathology were analyzed in the lung. Results Intranasal administration of silica recapitulated the key pathological features of human silicosis, including nonresolving inflammation, the formation of silicotic nodules, and diffuse lung fibrosis. A reporter mouse placed under the native NLRP3 promoter revealed silica rapidly upregulated NLRP3 expression throughout the lung. NLRP3-deficient mice displayed marked early reductions in silica-induced IL-1β and IL-18 levels in the airways. Additionally, NLRP3 deficiency impaired the rapid infiltration of conventional Siglec-F − and fibrotic Siglec-F + neutrophils, which correlated with reduced levels of neutrophil elastase. Deficiency in acute NLRP3-mediated inflammation correlated with significantly reduced pulmonary transforming growth factor beta and alpha smooth muscle actin expression, tissue damage, and fibrosis in the chronic phase of disease progression. Importantly, this included reduced silicotic nodule size and cellularity. Conclusions These findings highlight a major detrimental role for the NLRP3 inflammasome in driving silica-induced pulmonary neutrophil infiltration, TGFβ-mediated myofibroblast activation, tissue damage, and fibrosis.